Arbetsterapeutiska interventioner och dess effekter för barn i åldern 5-12 år med Attention Deficit Hyperactivity Disorder. : En litteraturöversikt - Nilsson, Ida-Maria (2014)
The purpose of this study was that through examination of the literature examining the types of occupational therapy interventions that are made for children with ADHD aged 5-12 years, and the effect of these. A literature review was chosen as the method to examine the state of knowledge in the subject of ADHD. Literature search was conducted through the databases available at the university library at Luleå Technical University and seven articles were selected. The analysis showed that interventions targeted primarily toward supporting children with concentration, sedentary and strengthen cognitive difficulties. The results of this report describe examples of the types occupational therapy interventions designed for children with ADHD. The results also indicate that occupational therapy interventions have a positive effect on the difficulties that this client group experience in their daily activities. The conclusion of this study is that occupational therapy interventions for children with ADHD are effective, but more research is needed, particularly in Sweden and Scandinavia when few studies were found with this origin. Validerat; 20140616 (global_studentproject_submitter)